Digital leadership in meta-organizations? Emergence of a renewed relevance of leadership in the context of digitization - Freis, Tamara; Schröer, Andreas (Frontiers in Education, 2024)
In the face of uncontrollable complexity, the concept of a rational design of the organization is being replaced by the notion of an open future that is inherently unpredictable and unplanable. In rapidly changing environments, organizations and leaders are confronted with a constant stream of irritations and unexpected developments, that require ongoing attention. This prompts the question of whether the conceptualization of digital transformation as a paradigm shift also implies the need for new forms of leadership. The article analyzes the discourse on digital leadership and assesses the extent to which this concept relativizes leadership in the context of the evolution of leadership theory, which is characterized by a persistent process of modification and relativization of preceding concepts. Leadership concepts are not only responsive to general needs, but also vary according to specific contexts, such as non-profit leadership or leadership in social welfare organizations and metaorganizations. Results of a discourse analysis, which underscore the significance of adopting a complexity theory perspective on digital leadership, will therefore be contrasted with the initial findings of an empirical study on digitization in such meta-organizations. This allows for a discussion of the general findings on the revitalization of leadership, which will serve as a paradigmatic example of the previously developed context. The article concludes with implications for further theory development with the aim of making a specific contribution to organizationsensitive digitization research. The findings of the empirical study indicate the significance of employing informal structures and a heightened emphasis on subjectivity within meta-organizations, as opposed to the formal structures of organizations. The concept of digital leadership does not signify the obsolescence of traditional leadership; rather, it can be conceptualized as an advanced form of unheroic leadership within the context of external and internal complexity.